The Dynamics of Social Movements in Unrecognized States—A Comparative Study - Ulas, Hilmi (Frontiers in Political Science, 2021)
In the political realm, our world is currently experiencing both a massive decline in democracies as well as the quality of democratic regimes in all geographical regions, and a rise in pro-democracy social change movements. Meanwhile, extant scholarly research emphasizes that social movements can contribute to changes in political regimes, such as the undermining of authoritarian ones or simply causing a circulation of the elite. Nevertheless, there is a gap in the scholarly knowledge regarding when political activism becomes effective or can even take place without total annihilation in the context of unrecognized states. To address this gap, studying cases of pro-democracy movements in unrecognized states through a comparative schema is the most effective methodology. In these cases, some variables that affect movement outcomes, such as international diplomatic relations, NGO activity, multinational company pressures, etc. are more restricted due to these states lacking official diplomatic capacity. Therefore, in unrecognized states, domestic political-economic factors are primal and their effects can be observed much more easily, which then lends some tentatively generalizable insights as well. For the purposes of this paper, I will consider the emergence and ultimate outcomes of pro-democracy movements in three unrecognized states: North Cyprus, Abkhazia, and Taiwan. All three cases in comparative perspective can shed light on the dynamics of how nonviolent, pro-democracy movements unfold under the authoritarian-leaning settings of unrecognized states with minimal international interaction or oversight.